THE IMPORTANCE OF VOCABULARY WORK IN LEARNING THE RUSSIAN LANGUAGE FOR NON-LANGUAGE GROUPS - Kamola Abdullayevna Shokarimova (American Journals, 2022)
The article discusses the optimal types of tasks and exercises that help students to effectively enrich their vocabulary in the Russian language textbook. In addition to the use of traditional types of vocabulary work, innovative ways to increase vocabulary that develop speech and broaden teachers' worldviews are also demonstrated.
Keywords: dictionary work, new words, vocabulary, innovative methods, speech content, translation, phraseology